Diagnostic value of lncRNA NORAD in pulmonary tuberculosis and its regulatory role in Mycobacterium tuberculosis infection of macrophages. (7th July 2022) - Sun, Wenna; He, Xiong; Zhang, Xiushuang; Wang, Xiaomeng; Lin, Wen; Wang, Xiaofeng; Liang, Yan
Abstract: Pulmonary tuberculosis (PTB) infection is a chronic inflammatory response caused by Mycobacterium tuberculosis ( Mtb ). The purpose of this study was to confirm the value of long noncoding RNA NORAD (noncoding RNA activated by DNA damage) in the diagnosis of PTB and to explore its mechanism in Mtb‐ infected macrophages. NORAD serum levels were estimated by qRT‐PCR in 90 patients with PTB and 85 healthy individuals. Receiver operating characteristic curves were plotted to assess the diagnostic value of NORAD in PTB. Human and murine macrophages were infected with Mtb strain H37Rv. CCK‐8 (a cell counting kit) and ELISA detected viability of macrophages and inflammatory cytokine secretion, respectively. A dual‐luciferase reporter assay was performed to analyze the relationship between NORAD and microRNA (miR)‐618. NORAD was significantly elevated in patients with PTB, and its positivity was correlated with levels of inflammatory cytokines IL‐1 β ( r = 0.854), TNF‐α ( r = 0.617), and IL‐6 ( r = 0.585). With an area under the curve of 0.918, and sensitivity and specificity of 80.0% and 89.4%, respectively, NORAD remarkedly differentiated patients with PTB from healthy individuals. Furthermore, Mtb infection significantly increased NORAD levels in THP‐1 and RAW264.7 cells and increased their viability and inflammation ( P < 0.001). However, this increased effect was weakened by reduced NORAD levels. Dual‐luciferase reporter assay results confirmed that miR‐618 in macrophages is a target miRNA for NORAD and can be negatively regulated by it. Moreover, elevated miR‐618 suppressed macrophage viability and inflammation in Mtb infection. NORAD is a potential diagnostic biomarker for PTB and is involved in Mtb ‐infected macrophage activity and inflammation by targeting miR‐618.